Originally Posted by

**sigma1** i think i may have go this one

$\displaystyle \frac{4u^2+3u-2}

{(u+1)(2u+3)}$

$\displaystyle 4u^2+3u-2=A(2u+3)+B(u+1)$

letting u -1 i solve the equation by eliminating B to get a value for A which is -1 ..... A= -1

letting u -1.5 i solve the equation by eliminating A to get a value for B which is -5 ..... B= -5

partial fraction =

$\displaystyle \frac{-1}

{(u+1)}$ +

$\displaystyle \frac{-5}

{(2u+3)}$

now all i have to do is diffrenciate that. think the quotient rule is needed there.. any help?